PHYSICAL AND CHEMICAL ATTRIBUTES OF SOIL AFFECTED BY MUNICIPAL SOLID WASTE DEPOSITION IN JARAGUÁ/BRAZIL - Félix, Robson Oliveira; Carneiro da Silva Teixeira, Gisele; Reis, Diana Rosa; Teixeira, Itamar Rosa (Geoambiente On-line, 2023)
The proper destination of Municipal Solid Waste (MSW) has been the subject of countless discussions, not only among scholars in the area, but also in public policies that seek ways to reduce environmental impacts arising from the inadequate final destination of this waste. This work aimed to evaluate the physicochemical characteristics of the soil and possible contaminations by pollutant metals in a definitive deposition site of MSW in Jaraguá-Goiás. The sampling arrangement was defined in a 3x3 scheme, with three soil covers (L - dump, M - upstream, J - downstream) and three depths (2, 4, and 6m). The following physical-chemical soil parameters were evaluated: particle size, water pH, O.M., CEC, Ca, Mg, P, K, Cu, Fe, Mn, Zn, and the pollutants Cd, Pb, and Cr. The results indicated that the samples from the MSW deposition site analyzed are not contaminated, considering the limits established by Conama and Cetesb. However, these values showed a significant difference between the landfill, upstream, and downstream samples, which were statistically proven by a 5% probability analysis. The chemical attributes, such as Ca, Mg, K, Fe, Cr, Cu, Mn, and pH were found to have higher concentrationsin the landfill samples, while Pb, P, and Zn had higher contents in the upstream points.